Jejak pemikiran B.J. Habibie : peradaban teknologi untuk kemandirian bangsa - Habibie, B. J. (Bacharuddin Jusuf), 1936-; Makka, A. Makmur, 1945- (Bandung : Mizan Pustaka : Didistribusikan oleh Mizan Media Utama, 2010)
Thoughts of Bacharuddin Jusuf Habibie on technology in Indonesia.
Includes bibliographical references (p. 335-344) and index.
Keywords: Habibie, B. J. -- 1936-; Technology and state -- Indonesia